Valuing Research leads: Bioprospecting and the Conservation of Genetic Resources - Rausser, Gordon C.; Small, Arthur A. (Journal of Political Economy, 2000)
Bioprospecting has been touted as a source of finance for biodiversity conservation. Recent work has suggested that the bioprospecting value of the “marginal unit” of genetic resources is likely to be vanishingly small, creating essentially no conservation incentive. This result is shown to flow specifically from a stylized description of the research process as one of brute‐force testing, unaided by an organizing scientific framework. Scientific models channel research effort toward leads for which the expected productivity of discoveries is highest. Leads of unusual promise then command information rents, associated with their role in reducing the costs of search. When genetic materials are abundant, information rents are virtually unaffected by increases in the profitability of product discovery and decline as technology improvements lower search costs. Numerical simulation results suggest that, under plausible conditions, the bioprospecting value of certain genetic resources could be large enough to support market‐based conservation of biodiversity.